PTH-152 Heller's myotomy and pneumatic dilatation in the treatment of achalasia: a population-based case-control study assessing long-term quality of life. (22nd June 2015) - Gray, RT; Coleman, HG; Lau, KW; McCaughey, C; Coyle, PV; Murray, LJ; Johnston, BT
Abstract : Introduction: Health-related quality of life (HRQL) is an important outcome measure in the treatment of achalasia yet long-term HRQL outcomes have not been widely reported. The aims of this study were to examine long-term disease-specific and general HRQL in achalasia patients using a population-based case-control method, and to assess HRQL between treatment interventions. Method: Manometrically diagnosed achalasia cases (n = 120) were identified and matched with controls (n = 115) using a population-based approach. Study participants completed validated general (SF-12) and disease-specific (Achalasia Severity Questionnaire [ASQ]) HRQL questionnaires, as appropriate, as part of a structured interview. Mean composite scores for SF-12 (mental component summary [MCS-12] and physical component summary [PCS-12]) and ASQ were generated and compared between cases and controls, or intervention groups, using an independent t -test. Age- and sex-adjusted mean differences in HRQL scores were also evaluated using a linear regression model. Results: Achalasia cases were treated with a Heller's myotomy (overall n = 43, laparoscopic n = 21), pneumatic dilatation (n = 44), or both modalities (n = 33). The median time from last treatment to HRQL assessment was 5.7 years (IQR 2.4–11.5). Comparing achalasia patients with controls, PCS-12 was significantly worse (40.9 vs . 44.2, P = 0.01) but MCS-12 was similar. However, both PCS-12 (39.9 vs . 44.2, P = 0.03) and MCS-12 (46.7 vs . 53.5, P = 0.004) were significantly impaired in those requiring dual treatment. Overall, there was no difference in adjusted HRQL measures between patients treated with Heller's myotomy and/or pneumatic dilatation. However, in the subgroup of patients undergoing laparoscopic Heller's myotomy, general HRQL scores were similar to the population controls. ASQ was also significantly better in the laparoscopic group compared to pneumatic dilatation (adjusted mean difference 12.2, [95% CI 1.8, 22.7]). Conclusion: Despite treatment, achalasia patients have significantly worse long-term physical HRQL compared to population controls. Poor HRQL is most pronounced in patients requiring dual treatment where mental and physical HRQL are significantly impaired. Overall, no long-term HRQL differences were observed between the treatment modalities. However, laparoscopic Heller's myotomy may confer a benefit and further studies with long-term follow-up are warranted. Disclosure of interest: None Declared.